2020
DOI: 10.3389/fimmu.2020.588411
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive Cellular and Metabolic Reprogramming in Porcine Lung Mononuclear Phagocytes Infected With Type 1 PRRSV Strains

Abstract: Porcine reproductive and respiratory syndrome (PRRS) has an extensive impact on pig production. The causative virus (PRRSV) is divided into two species, PRRSV-1 (European origin) and PRRSV-2 (North American origin). Within PRRSV-1, PRRSV-1.3 strains, such as Lena, are more pathogenic than PRRSV-1.1 strains, such as Flanders 13 (FL13). To date, the molecular interactions of PRRSV with primary lung mononuclear phagocyte (MNP) subtypes, including conventional dendritic cells types 1 (cDC1) and 2 (cDC2), monocyte-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 78 publications
2
4
0
Order By: Relevance
“…First, we compared the WT libraries against mock ( Figure 11A , Figure 11—source data 1 ) and the KO2 libraries against mock ( Figure 11B , Figure 11—source data 2 ). Similarly to other studies ( Pröll et al, 2017 ; Badaoui et al, 2013 ; Crisci et al, 2020 ), we found transcription of genes related to regulation of the cell cycle (amongst other GO terms) to be perturbed by WT PRRSV infection ( Figure 11—source data 1 , sheet: ‘GO_TS_up’; GO term GO:0051726 ~26-fold enriched in transcriptionally upregulated genes). However, a comparison of transcriptional fold changes with those of TE reveals that the majority of transcriptionally upregulated genes in WT or KO2 compared to mock are downregulated in terms of TE ( Figure 11A and B , top-left quadrants of right-column panels).…”
Section: Resultssupporting
confidence: 86%
“…First, we compared the WT libraries against mock ( Figure 11A , Figure 11—source data 1 ) and the KO2 libraries against mock ( Figure 11B , Figure 11—source data 2 ). Similarly to other studies ( Pröll et al, 2017 ; Badaoui et al, 2013 ; Crisci et al, 2020 ), we found transcription of genes related to regulation of the cell cycle (amongst other GO terms) to be perturbed by WT PRRSV infection ( Figure 11—source data 1 , sheet: ‘GO_TS_up’; GO term GO:0051726 ~26-fold enriched in transcriptionally upregulated genes). However, a comparison of transcriptional fold changes with those of TE reveals that the majority of transcriptionally upregulated genes in WT or KO2 compared to mock are downregulated in terms of TE ( Figure 11A and B , top-left quadrants of right-column panels).…”
Section: Resultssupporting
confidence: 86%
“…First, we compared the WT libraries against mock (Figure 11A, Supplementary Table 9) and the KO2 libraries against mock (Figure 11B, Supplementary Table 10). Similarly to other studies 79,86,87 , we found transcription of genes related to regulation of the cell cycle (amongst other GO terms) to be perturbed by WT PRRSV infection (Supplementary Table 9, sheet: 'GO_TS_up'; GO term GO:0051726 ~26-fold enriched in transcriptionally up-regulated genes). However, a comparison of transcriptional fold changes with those of TE reveals that the majority of transcriptionally up-regulated genes in WT or KO2 compared to mock are down-regulated in terms of TE (Figure 11A and B, top-left quadrants of right-column panels).…”
Section: Host Differential Gene Expression At 12 Hpisupporting
confidence: 84%
“…Swine DC have been identified in tonsils (Soldevila et al, 2018), tracheal epithelium and pulmonary parenchyma (Maisonnasse et al, 2016). They can be divided in cDC1, cDC2 and moDC whose RNAseq signatures cluster with their mouse spleen and/or lung counterparts (Crisci et al, 2020). Plasmacytoid DC have also been identified in swine tonsil, they are E2.2 and IRF7 positive as observed in mouse and man.…”
Section: Dendritic Cellsmentioning
confidence: 97%
“…PIM are resident lung intravascular macrophages intimately tight with endothelial cells, what differentiates them from marginated blood monocytes (for review see (Kuebler and Goetz, 2002)). We recently isolated porcine PIM and demonstrated that they were very similar to AM (Bordet et al, 2018;Crisci et al, 2020), indeed PIM and AM overexpressed genes such as PU.1 and HDAC10, leading us to suggest than PIM were, like AM, self-renewable embryonically derived macrophages, and/or that PIM may directly originate from AM (Bordet et al, 2018). PIM have been involved in acute lung inflammation in Laurasiatheria species (Cantu et al, 2007;Singh et al, 2004).…”
Section: Macrophagesmentioning
confidence: 99%